Effect of Korean Red Ginseng supplementation on dry eye syndrome in glaucoma patients – A randomized, double-blind, placebo-controlled study - Hyoung Won Bae; Ji Hyun Kim; Sangah Kim; Minkyo Kim; Naeun Lee; Samin Hong; Gong Je Seong; Chan Yun Kim (Journal of Ginseng Research, 2015)
Background: Many patients with glaucoma have difficulty using antiglaucoma eye drops because of dry eye symptom. In this prospective, randomized, double-blind, placebo-controlled study, we evaluated the effect of Korean Red Ginseng on dry eye syndrome in patients with glaucoma treated with antiglaucoma eye drops. Methods: Forty-nine participants were allocated to the Korean Red Ginseng (3 g/day; n = 24) or placebo (n = 25) groups for 8 weeks. Tear film stability, fluorescein corneal staining, conjunctival hyperemia, tear production, grade of meibomian gland dysfunction, and dry eye questionnaire (Ocular Surface Disease Index) were evaluated at baseline and on completion of the treatment. Results: Almost all patients displayed dry eye symptoms and signs at baseline. After the 8-week intervention, Korean Red Ginseng supplementation significantly improved the tear film stability and total Ocular Surface Disease Index score, as compared to placebo (p < 0.01). Conclusion: Korean Red Ginseng supplementation may provide an additional treatment option for dry eye and patients with glaucoma using antiglaucoma eye drops.